P009 Australian consultant pharmacists' potential roles in sleep health care - Exploring a new avenue for improving the management of insomnia. (7th October 2021) - Basheti, M; Tran, M; Wong, K; Gordon, C; Grunstein, R; Saini, B
Abstract: Background: Insomnia is a highly prevalent sleep disorder and the first-line recommended treatment is cognitive behavioural therapy. However, there is persistent use of pharmacotherapy, mainly, sedative-hypnotics. Consultant pharmacists can provide medication review services for patients on polypharmacy, and are therefore well placed to educate patients and provide sleep health/insomnia care with regards to pharmacotherapy and behavioural therapy use. Objectives: To explore consultant pharmacists' current sleep health-related practice and what their perspectives are around developing/implementing a consultant pharmacist-led behavioural service for insomnia. Methods: Qualitative semi-structured interviews were conducted with a convenience-based sample of consultant pharmacists. Interviews were audio-recorded, transcribed and thematically analysed. Results: Twenty-four consultant pharmacists were interviewed. Three themes were gauged: 1) Trivializing insomnia and sleep health, 2) Patients – an integral piece of the treatment puzzle, 3) Making it work. Participants commonly dealt with older patients and frequently encountered patients with sleep complaints/consuming sleep aids. Generally, it was believed that sleep health was considered a 'non-priority', with other comorbidities taking precedence in health provisions. While interested in expanding their sleep health/insomnia practice, participants expressed the need for appropriate education/training, funding and collaborative treatment configurations. Further, patients' attitudes towards treatment approaches were regarded critical to future service developments. Conclusion: Insomnia/sleep health concerns are growing. Primary health professionals need to scale up their sleep health care provisions to accommodate for this health demand. Consultant pharmacists are interested/willing to expand their sleep-related practice and provide evidence-based insomnia therapies, however factors such as education/training, service configuration support and patient attitudes should be addressed.